2022
DOI: 10.1590/1806-9282.20211040
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle sequelae in young university students infected by coronavirus disease 2019: an observational study

Abstract: BACKGROUND:The infection caused by coronavirus disease 2019 can lead to respiratory sequelae in individuals who have experienced severe or mild symptoms. METHODS: An observational, cross-sectional study was developed, following the STROBE guidelines. Maximal inspiratory and expiratory mouth pressures were assessed in 50 healthy young students (26 women, 24 men; age 22.20±2.41 years). The inclusion criteria were as follows: aged between 18 and 35 years; control group: not diagnosed with coronavirus disease 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
7
2
Order By: Relevance
“…In our study, both inspiratory (50%) and expiratory (66.7%) muscle strength were found as weakened according to the long-term results of young individuals who had mildly recovered from COVID-19. In contrast to the present study, Plaza and Sevilla [ 21 ] showed preserved respiratory muscle strength in university students who had recovered from mild COVID-19 at least 6 months later; however, they showed that the inspiratory muscle strength of individuals with COVID-19 decreased compared to healthy individuals, but the expiratory muscle strength did not change. The difference between respiratory muscle strength results may be due to the female gender dominance in this study, unlike the Plaza and Sevilla study [ 21 ] because the subgroup results showed that the respiratory muscle strength of women with COVID-19 decreased more [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our study, both inspiratory (50%) and expiratory (66.7%) muscle strength were found as weakened according to the long-term results of young individuals who had mildly recovered from COVID-19. In contrast to the present study, Plaza and Sevilla [ 21 ] showed preserved respiratory muscle strength in university students who had recovered from mild COVID-19 at least 6 months later; however, they showed that the inspiratory muscle strength of individuals with COVID-19 decreased compared to healthy individuals, but the expiratory muscle strength did not change. The difference between respiratory muscle strength results may be due to the female gender dominance in this study, unlike the Plaza and Sevilla study [ 21 ] because the subgroup results showed that the respiratory muscle strength of women with COVID-19 decreased more [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the present study, Plaza and Sevilla [ 21 ] showed preserved respiratory muscle strength in university students who had recovered from mild COVID-19 at least 6 months later; however, they showed that the inspiratory muscle strength of individuals with COVID-19 decreased compared to healthy individuals, but the expiratory muscle strength did not change. The difference between respiratory muscle strength results may be due to the female gender dominance in this study, unlike the Plaza and Sevilla study [ 21 ] because the subgroup results showed that the respiratory muscle strength of women with COVID-19 decreased more [ 21 ]. In addition, the inclusion of individuals with asymptomatic COVID-19 in the study [ 21 ] may explain the preservation of respiratory muscle strength, as it is thought to reduce the severity and effect of the disease.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…After hospital discharge, this muscle weakness persists in 92% of patients [6]. During the course of the disease, symptoms are often persistent and impactful, and muscle weakness seems to impair lung function and maximal inspiratory pressure (MIP) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%